Biomimetic scaffolds based on hydroxyethyl cellulose for skin tissue engineering - Farah Hanani, Zulkifli (2015)
Research using biomaterials as scaffolds in skin tissue engineering is tremendously increasing as these biomaterials have been found to mimic the structure of extracellular matrix (ECM) that provides a platform for cell attachment, differentiation and proliferation. Hydroxyethyl cellulose (HEC) is modified cellulose, one of the most abundant natural polymers in the world. The advantage of HEC is its chemical structure, which exactly matches that of glycosaminoglycan (GAG) in the dermis. The focus of this research is to develop scaffolds based on HEC for skin tissue engineering. Two techniques were used to fabricate scaffolds, which are electrospinning and freeze-drying. Electrospinning produces fibers in nanometer scale and interconnected pores that closely resemble the topography features of ECM. Freeze-drying is an easy and convenient technique to produce highly interconnected pores, favourable in tissue engineering. This report comprised of two parts. The first part is about the fabrication and characterization of scaffolds using electrospinning and freeze-drying techniques while the second part is the cell culture studies of nanofibers and freeze-dried scaffolds. In the first part, there are four different studies conducted based on HEC polymers. The first study is on the effect of cross-linking effect on HEC/PVA and HEC/PVA/collagen nanofiber scaffolds prepared by electrospinning method. The concentration of HEC (5%) with PVA (15%) was optimized, blended in different ratios (30-50%) of HEC content and electrospun to obtain smooth nanofibers. The fabrication of HEC/PVA/collagen (0.38%) was also reported. Nanofibers were made water insoluble through chemical cross-links using glutaraldehyde. The microstructure, morphology, mechanical and thermal properties of the HEC/PVA and HEC/PVA/collagen nanofibrous scaffolds was characterized via SEM, ATR-FTIR, DSC, UTM and TGA. The second is the in vitro degradation study aimed to investigate the behaviour of electrospun HEC/PVA and HEC/PVA/collagen nanofibrous scaffolds in two biologically related media: phosphate buffered solution (PBS) and Dulbecco’s modified Eagle’s medium (DMEM) for a 12-week incubation period. The results showed that HEC/PVA/collagen scaffolds degraded slower in both media than HEC/PVA scaffolds. All fibers displayed uneven and rough surfaces towards the final week of incubation periods. As degradation time increased, the thermal studies revealed that the melting temperatures and crystallinity of the scaffolds slightly shifted to a lower value. Both HEC/PVA and HEC/PVA/collagen fibers showed a significant decrease in Young’s modulus and tensile stress over the 12-week degradation. The third study is fabrication of biopolymeric scaffolds of HEC and PVA using freeze-dry technique and characterized based on their potential for skin tissue engineering. The pore size of HEC/PVA blended scaffolds (2 - 40 μm) showed diameters in the range of both pure HEC (2 - 20 μm) and PVA (14 - 70 μm) scaffolds. All porous scaffolds revealed porosity above 85 %. The water uptake and degradation rate of HEC scaffolds could be controlled by incorporation of PVA in the blends. The ATR-FTIR results exhibit possible interactions between hydroxyl groups of HEC and PVA in the blends. TGA/DrTGA curves clarified different major steps of weight loss involved with different scaffolds. The Tg values of HEC/PVA of the DSC curve occur in the range of HEC and PVA, which represents the miscibility of HEC/PVA blend polymers. Higher Young’s modulus was obtained by increasing the HEC content. The forth study is the fabrication of novel HEC/silver nanoparticles (AgNPs) formed via the freeze-drying using mixture of HEC and AgNO3 where HEC acts as the reducing agent to silver nanoparticles. Scaffolds from HEC/AgNPs composites were successfully prepared with average pore size ranging from 50 to 150 μm. The surface Plasmon resonance, which shows absorption peaks in the range of 417 – 421 nm, validates the presence of silver nanoparticles in the HEC matrices. The HEC/AgNPs scaffolds showed significance porosity of more than 80 % and a high degree of swelling ratio properties. The DSC thermogram showed augmentation in Tg with the increase of Ag content. The second major part of this work showed cytotoxicity studies based on investigation of morphology and cell proliferation of scaffolds using SEM and MTT/MTS assays. Cell-scaffolds interaction demonstrated that melanoma and human fibroblast (hFB) cells differentiated and spread well on scaffolds with better cell proliferation and attachment with time, appeared more prominent on HEC/PVA/collagen nanofibers, HEC/PVA freeze-dried and HE/AgNPs (1.6%) scaffolds. Since these biocompatible and biodegradable scaffolds showed promising results, these scaffolds could be adopted for the design of next-generation tissue engineered skin grafts or wound dressing.